PERSEPSI MASYARAKAT NEGERI SULI DI KABUPATEN MALUKU TENGAH TENTANG KONSUMSI Nerita Sp. (Gastropoda) - Kurnia, Tri Santi; Sumah, Vonissa; Liline, Sintje; Salmanu, Sriyanti Imelda A (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2021)
Background: The coastal waters of Suli Village, Central Maluku Regency, have a promising source of animal protein, especially from the gastropod invertebrates of the genus Nerita, the species Nerita Chamaeleon. This research was conducted to determine the perception of the people of Suli Village in Central Maluku Regency about the consumption of Nerita sp. Methods: This research is a descriptive study with the research instrument in the form of a questionnaire using a Likert scale which was distributed to 60 (sixty) respondents. The research data were processed using Microsoft Excel 2010 and presented in graphical form. Results: A total of sixty (60) respondents gave answers to fifteen (15) questions listed in the questionnaire. The result is that the average score obtained is quite varied. The average score obtained for each question item is; 1st question 3.8, 2nd question 4, 3rd question 3.6, 4th question 3.4, 5th question 3.1, 6th question 3.7, 7th question 3.4, question 8th question is 3.6, 9th question is 3.6, 10th question is 3.8, 11th question is 3.9. the 12th question is 3.8, the 13th question is 4.2, the 14th question is 3.7, and the 15th question is 4.3. Conclusion: The results of the study show that only a small proportion of the people of Suli Village consume Nerita sp. This happened because of the body size factor of Nerita sp. which is too small and the processing takes time, as well as the assumption that Nerita sp. can increase the risk of hypertension in the elderly.